2011
DOI: 10.1089/jwh.2010.2036
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variance of Cardiovascular Risk Factors Among Community Women: The National Sister to Sister Campaign

Abstract: In a large, community-based sample of women nationwide, this comprehensive analysis shows remarkable geographic variation in risk factors, which provides opportunities to improve and reduce a woman's CVD risk. Further investigation is required to understand the reasons behind such variation, which will provide insight toward tailoring preventive interventions to narrow gaps in CVD risk reduction in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Geographic variance in the prevalence of cardiovascular risk factors in the population occurs in the United States, 22,23 Canada, 24 and Europe. 25,26 In addition, national and regional variance in such risk factors have been observed in global surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Geographic variance in the prevalence of cardiovascular risk factors in the population occurs in the United States, 22,23 Canada, 24 and Europe. 25,26 In addition, national and regional variance in such risk factors have been observed in global surveys.…”
Section: Discussionmentioning
confidence: 99%
“…underlined that multiple factors make up a community, such as racial and ethnic majorities, education, and income, in addition to local conditions that affect lifestyle, such as climate, grocery stores, transportation, safety and availability of parks and open spaces. Therefore, regional variation is likely to reflect the complex interplay between a region and the inhabiting population [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Among a few similar studies, important geographical disparities in cardio metabolic risk factors have been reported in Europe [29] and worldwide [9][10][11][12][13][14]. To our knowledge, this is the first most comprehensive study to address the spatial effect of top leading behavioural and cardio metabolic risk factors in Luxembourg.…”
Section: Discussionmentioning
confidence: 71%
“…Recently, evidence regarding geographic variations in cardiovascular risk profiles was reported among provinces in Canada [9], among women in cities of the United States [10], between southern and northern populations of China [11], in Malaysia [12] and in African populations [13,14]. Studies have found that risk factors tend to cluster within socially disadvantaged regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation